Comprehensive analysis of a three-phase DC–DC resonant converter with an open delta-wye transformer using variable frequency - Santos, Kristian Pessoa dos (2021)
A three-phase soft-switched DC–DC resonant converter with variable frequency to perform the output voltage control is proposed. The open delta-wye connection provides a double output voltage reducing the primary current stress, turns ratio, weight and volume of high-frequency transformer. To achieve high efficiency, an LLC resonant tank is designed so that all switches can perform zero-voltage switching for the entire power range. In order to verify the operating principle of the converter, a design example is described, with the following converter specifications: input voltage 96 V, output voltage 380 V and a switching frequency up to 120 kHz. The feasibility and practicality of the proposed converter are confirmed by experimental results with a 1.5 kW prototype.